Preparation of active antibacterial LDPE surface through multistep physicochemical approach II: graft type effect on antibacterial properties - Bílek, František; Sulovská, Kateřina; Lehocký, Marián; Sáha, Petr; Humpolíček, Petr; Mozetič, Miran; Junkar, Ita (Colloids and surfaces. B, Biointerfaces, 2013)
Three monomers (allylamine, N-allylmethylamine and N,N-dimethylallylamine) were used for grafting onto air plasma activated LDPE surface. Antibacterial agent triclosan was anchored on such substrates. Influence of graft type on the antibacterial properties was determined. Increase of antibacterial activity and amount of deposited antibacterial agent for N-allylmethylamine and N,N-dimethylallylamine monomers were examined. Surface characteristics were measured by means of static contact angle measurement with surface energy evaluation, ATR-FTIR spectroscopy, XPS and SEM characterization analysis. Antibacterial properties were tested in vitro by inhibition zone method on agar plates for Staphylococcus aureus and Escherichia coli strains.
Keywords: antibakteriální látky; allylamin; polyethylen; Microscopy, Electron, Scanning; Spectroscopy, Fourier Transform Infrared; Allylamine; Escherichia coli; mikroskopie elektronová rastrovací; Anti-Bacterial Agents; Staphylococcus aureus; spektroskopie infračervená s Fourierovou transformací; Polyethylene